2014
DOI: 10.3140/bull.geosci.1472
|View full text |Cite
|
Sign up to set email alerts
|

New insectivores (Lipotyphla, Mammalia) from the Late Miocene of the Sivas Basin, Central Anatolia

Abstract: The ages of the rich Central Anatolian Late Miocene mammal sites Hayranlý 1 and Düzyayla are only approximately known. One of the main reasons for the age uncertainties is the substantial faunal difference between Anatolia and Europe during this time slice, hampering correlations to the European MN system. Previously, a MN 10 or MN 11 age has been assigned to Hayranlý 1 (Anatolian Zone J) and a MN 12 age to Düzyayla (Zone K) based on rodents. Here we studied the fossil insectivores from these two Turkish Mioce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…These morphological features, but also the size of the examined dental elements, fit well with those reported for P. hungarica (Reumer, 1984;Rzebik-Kowalska, 1989, Marchetti et al, 2000Popov, 2003;Siori et al, 2014). The size of the teeth is larger than that of Petenyia dubia, a species reported in several Miocene and Pliocene localities of Europe (Bachmayer and Wilson, 1970;Furió et al, 2014), whereas Petenyia katrinae is only documented in the early Yushean (early Pliocene) of Eastern Asia (Qiu and Storch, 2000). If confirmed, this would be the oldest Italian record of this soricid.…”
Section: Vertebratessupporting
confidence: 75%
“…These morphological features, but also the size of the examined dental elements, fit well with those reported for P. hungarica (Reumer, 1984;Rzebik-Kowalska, 1989, Marchetti et al, 2000Popov, 2003;Siori et al, 2014). The size of the teeth is larger than that of Petenyia dubia, a species reported in several Miocene and Pliocene localities of Europe (Bachmayer and Wilson, 1970;Furió et al, 2014), whereas Petenyia katrinae is only documented in the early Yushean (early Pliocene) of Eastern Asia (Qiu and Storch, 2000). If confirmed, this would be the oldest Italian record of this soricid.…”
Section: Vertebratessupporting
confidence: 75%
“…Thus, there is a significant faunal exchange from forest dwellers to ground-dwelling species, which is characterized by the increase in Myomimus finds from a number of localities during the Late Miocene, probably attributable to the vegetational shift from predominating forested wetland environments to open woodland and steppe-like environments. Furthermore, Furio et al (2014) found an almost identical faunal content of the localities from Hayranlı (58-Hay/80-82-83-84-85), including 1 erinaceid (Schizogalerix sinapensis), 5 soricids (including Paenelimnoecus sp., Amblycoptus oligodon, Petenyia dubia, Soricinae indet., and Crocidurinae/Crocidosoricinae indet. ), and 2 talpids (Desmanella aff.…”
Section: Biochronology and Paleobiogeography Of The Sivas Fossil Bedsmentioning
confidence: 94%
“…The insectivore assemblage is typical for the Late Miocene. It points to an Early or Middle Turolian (MN11-12) age (Furio et al, 2014). Additionally, during this time-span, a significant number of hominoids appeared, representing Ankarapithecus meteai and Ouranopithecus turkae in Anatolia.…”
Section: Biochronology and Paleobiogeography Of The Sivas Fossil Bedsmentioning
confidence: 99%
See 2 more Smart Citations